Nutraceutical Alternatives to Pharmaceutical Analgesics in Osteoarthritis - Shane Heffernan (Pain Management - Practices, Novel Therapies and Bioactives, 2021)
Chronic pain is a considerable health concern worldwide, effecting almost 30% of all European adults. Osteoarthritis (OA), a progressive pro-inflammatory condition, is one of the leading causes of chronic pain (effecting 13% of all ﻿those over 50 years, globally) and is the most common cause of joint pain. The prevalence of non-steroidal anti-inflammatory drug (NSAIDs) and analgesic use has been well studied and is abundant throughout the western world, with women being the greatest users and ibuprofen generally being the most ﻿reported NSAID. In the US, 65% of all OA patients are prescribed NSAIDs for pain management and form part of the current recommended strategy for OA clinical management. While some NSAIDs and analgesics are effective at improving pain and physical function, they come with significant and harmful side effects such as gastrointestinal complications, renal disturbances and severe cardiovascular events. Given these side-effects, any reduction in NSAID and analgesia use (and the resulting potentially harmful side effects) is of particular importance to OA public health. As such, a number of non-pharmaceutical alternatives (bioactive nutraceuticals) have been developed that may reduce NSAID and analgesia use while maintaining pain reduction and improvements in physical function. This chapter will discuss select nutraceuticals that are not currently in mainstream use but may have the potential to aid in the treatment of OA.